Creature teacher : the final exam - Stine, R. L. (New York, N.Y. : Scholastic Inc., 2014)
When Tommy is sent to a special camp to make him into a "winner," he discovers that his fellow campers are competitive to the point of obsession, and that a particular teacher, Mrs. Maargh, takes winning very seriously.
The most wanted list continues with a special edition inside.
Appeals to 4th-6th graders.
Reading level grade 4.
Keywords: Camps -- Juvenile fiction; Competition -- Juvenile fiction; Success -- Juvenile fiction; Self-realization -- Juvenile fiction; Camps -- Fiction; Success -- Fiction; Winning and losing -- Juvenile fiction; Horror stories; Horror tales